Preoperative standardized phase angle at bioimpedance vector analysis predicts the outbreak of antimicrobial-resistant infections after major abdominal oncologic surgery: a prospective trial - Roccamatisi, Linda; Gianotti, Luca; Paiella, Salvatore; Casciani, Fabio; De Pastena, Matteo; Caccialanza, Riccardo; Bassi, Claudio; Sandini, Marta (Nutrition, 2021)
Objectives - Infectious morbidity is the most common and costly among all surgery-related complications, and infections by multidrug-resistant microorganisms (MDR) are associated with poor outcomes. Derangements of body composition is a recognized risk factor for infections. The aim of this study was to investigate the potential association between specific traits of body composition and the risk of having MDR-related infections. - Methods - This was a prospective study with patients scheduled for major abdominal surgery for gastrointestinal cancer. Bioimpedance vector analysis (BIVA), a reliable tool for body composition assessment, was performed the day before the operation. Postoperative complications were collected focusing on resistance patterns and site of infection. Patterns of resistance were compared with BIVA parameters. - Results - Data from 182 patients suffering from pancreatic (n = 76, 41.7%), rectal (n = 38, 20.9%), gastric (n = 31, 17%), or hepatic (n = 37, 20.3%) malignancy were collected. Overall complications occurred in 108 patients (59%), and in 45 patients (28%) bacterial infections were proven at culture. Of these, 15 (8%) were multidrug-sensitive (MDS), 38 MDR, and 2 extended drug-resistant (XDR) infections. The standardized phase angle measured (SPA) at BIVA was significantly lower in the MDR/XDR infections (-0.02 ± 1.20) than for no infection/MDS (0.56 ± 1.53; P = 0.029). A multivariate analysis showed that SPA was the only independent variable for MDR/XDR infections with an odds ratio of 3.057 (95% confidence interval, 1.354-6903; P = 0.007). The predictive ability of SPA revealed an area under the receiver operating characteristic curve of 0.662, with an optimal threshold of -0.3. - Conclusions - In surgical cancer patients, preoperative value of SPA lower than -0.3 is associated with the outbreak of MDR bacterial infections.